Heparin immobilization onto segmented polyurethaneurea surfaces - effect of hydrophilic spacers - Park, K.D.; Okano, T.; Nojiri, C.; Kim, S.W.
Heparin was immobilized onto segmented polyurethane-urea surfaces (Biomer)using hydrophilic poly(ethy1ene oxide)spacers of different chain lengths. The use of the hydrophilic spacer, poly(ethy1ene oxide), reduces protein adsorption and subsequent platelet adhesion on the surface. In addition, the bioactivity of the immobilized heparin is enhanced by the incorporation of these spacers. Immobilized heparin bioactivity is shown to be a function of PEO spacer length. Use of hydrophilic PEO spacers demonstrates that immobilized heparin's bioactivity is consistently higher than that of the Co alkyl spacer, but heparinimmobilized surfaces demonstrate no chain length effect on platelet adhesion, even though they show less platelet adhesion compared to Biomer controls. In the case of PEO-grafted surfaces, platelet adhesion is decreased compared to Biomer controls, and C6 alkyl spacer-grafted surfaces, and exhibits a minimum at I'EO 1000. In ex ziivo A-A shunt experiments under low flow and low shear conditions, all heparinized surfaces exhibit significant prolongation of occlusion times compared to Biomer controls, indicating an ability of immobilized heparin to inhibit thrombosis in whole blood.